Pembuatan Indeks Artikel Surat Kabar Beranotasi Menggunakan Microsoft Access 2010 di Kantor Arsip, Perpustakaan, dan Dokumentasi Kota Padang - Oktaviani, Uci; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
In this article, how to manufacture indexes newspaper articles annotated using Microsoft Access 2010 in the Office of Arsip, Perpustakaan, dan Dokumentasi Kota Padang. newspaper articles index creation is done against a newspaper that contained in the Office of Arsip, Perpustakaan, dan Dokumentasi Kota Padang. Data obtained from newspaper clippings from the Library at the Arsip, Perpustakaan, and Dokumentasi Kota Padang in January and February were 63 titles article. Data in the form of newspaper articles Kompas, Singgalang, Haluan, and Padang Ekpres. Details of the findings are the 21 titles of the Kompas, from Singgalang 17 titles, 13 titles from the Haluan, and 12 titles from Padang Ekspres. Process in the preparation of an annotated index of newspaper articles were collected four newspaper titles, selecting articles, create a description of the article, make annotations, specify keywords, create indexes newspaper articles, indexing newspaper articles, newspaper articles compiled an annotated index, typing. After doing indexing articles, article index can then be copied into the program Microsoft Access 2010. Â Keywords: Ms. Acces; newspaper; article